1994
DOI: 10.1006/jfan.1994.1090
|View full text |Cite
|
Sign up to set email alerts
|

Operator Spaces and Residually Finite-Dimensional C*-Algebras

Abstract: For every operator space X the C * -algebra containing it in a universal way is residually finite-dimensional (that is, has a separating family of finitedimensional representations). In particular, the free C * -algebra on any normed space so is. This is an extension of an earlier result by Goodearl and Menal, and our short proof is based on a criterion due to Exel and Loring.1991 Mathematics Subject Classification. 46L05, 46B28, 46M15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Let M ⊂ B(H) be a subspace. We can associate to it a "free" C * -algebra C * M and a completely isometric linear map µ : M → C * M such that C * M = C * (µ(M)), and whenever ϕ : M → B(H ϕ ) is a completely contractive linear map, there is a unital * -homomorphism π ϕ : C * M → B(H ϕ ) with the property that π ϕ • µ = ϕ on M. Once again, C * M can be realized more concretely as the C *algebra generated by the image of M under an appropriate direct sum of completely contractive linear maps [36,Theorem 3.2].…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…Let M ⊂ B(H) be a subspace. We can associate to it a "free" C * -algebra C * M and a completely isometric linear map µ : M → C * M such that C * M = C * (µ(M)), and whenever ϕ : M → B(H ϕ ) is a completely contractive linear map, there is a unital * -homomorphism π ϕ : C * M → B(H ϕ ) with the property that π ϕ • µ = ϕ on M. Once again, C * M can be realized more concretely as the C *algebra generated by the image of M under an appropriate direct sum of completely contractive linear maps [36,Theorem 3.2].…”
Section: 1mentioning
confidence: 99%
“…Acknowledgements. The first author wishes to thank Matt Kennedy for a stimulating discussion which brought [36] to his attention and sparked his interest in the residual finite-dimensionality of C * -covers.…”
Section: Introductionmentioning
confidence: 99%
“…Pestov [17] once defined the universal C * -algebra of an operator space. Based on Pestov's idea on the universal C * -algebra of an operator space and the universal C * -algebra free product of C * -algebras (see ref.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, Choi [4] had shown that the full C* -algebra of the free group on two generators is RFD. The connections between freeness and the RFD property have been developed in [8,6,10]. In the course of this, Exel and Loring gave several equivalent conditions for the RFD property [6,Theorem 2.4].…”
mentioning
confidence: 99%
“…(iii) Pestov [10] has recently used the equivalence of (c) and (e). Spaces Rep(/1, H) have also been used recently in [1,9].…”
mentioning
confidence: 99%